Descriptions of Infertile Couple Attitudes About Nyo Khana Traditional Medicine - Sebtalesy, Cintika Yorinda; Kristanti, Lucia Ani (Jurnal Midpro, 2020)
Infertility or sterility is one of reproductive health problems that often develops into a social problem because the wife is always regarded as the cause. In 2011 demographic and health survey of East Java Province obtained the data amounting to 2% of infertile couples and in 2012 some 2.30% of the data is an increase of 0.30%. This study aims to determine variations in the treatment of infertile couples search pattern in traditional medicine Nyo Khana Magetan 2015.This research uses descriptive design. The population in this study are all infertile couples in treatment Nyo Khana Magetan as many as 45 pairs. With the sampling technique used purposive sampling, a number of 31 respondents. The instrument used was a questionnaire, analysis used is the mean ((X) Ì…) and percentage (%).The result showed the behavior of infertile couples to seek health care many who visit the health services of medical and non-medical, as 19 respondents (61.3%) and infertile couples who visit non-medical treatment as much as 12 respondents (38.7%).Â The conclusion that the existence of a wide variety of search patterns when the treatment of infertile couples find it difficult to conceive seek treatment to non-medical. The ordinances performed infertile couples when they have long not obtained a pregnancy which is seeking medical treatment in advance to find out the problems that exist in the womb.